2020
DOI: 10.1002/ece3.6263
|View full text |Cite
|
Sign up to set email alerts
|

Diet specialization and brood parasitism in cuckoo species

Abstract: Brood parasitism is a breeding strategy adopted by many species of cuckoos across the world. This breeding strategy influences the evolution of life histories of brood parasite species. In this study, we tested whether the degree on diet specialization is related to the breeding strategy in cuckoo species, by comparing brood parasite and nonparasite species. We measured the gradient of diet specialization of cuckoos, by calculating the Gini coefficient, an index of inequality, on the multiple traits describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Birds in nature also have similar behaviors [23]. Broodiness is essential for the breeding of wild birds [24], with the exception of brood parasitism by cuckoos [25]. The artificial domestication of geese is far from the effect in hens.…”
Section: Discussionmentioning
confidence: 99%
“…Birds in nature also have similar behaviors [23]. Broodiness is essential for the breeding of wild birds [24], with the exception of brood parasitism by cuckoos [25]. The artificial domestication of geese is far from the effect in hens.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the Cuckoo-finch (Anomalospiza imberbis), viduid finches specialise on estrildid finches (Estrildidae), which are not parasitised by cuckoos or honeyguides. This is possibly related to the granivorous diet of nestling estrildid finches (Jamie et al, 2021) compared to the typically insectivorous diet of cuckoos and honeyguides (Morelli et al, 2020;Short & Horne, 1985). Furthermore, there is little overlap in host species among Vidua species as speciation among members of this genus has been facilitated by host specialisation (Jamie et al, 2021;Sorenson et al, 2003).…”
Section: Global Patterns Of Brood Parasite-host Network Complexitymentioning
confidence: 99%
“…2019 ). It was also recently found that brood parasitic cuckoos have a higher degree of dietary specialization compared with nonparasitic cuckoos, although the mechanisms behind this association are unknown ( Morelli et al. 2020 ).…”
Section: The Study System: Avian Brood Parasitismmentioning
confidence: 99%